PREHOSPITALNO DETEKTOVAN ACUTNI INFARKT MIOKARDA SA ST ELEVACIJOM KOD COVID 19 POZITIVNOG PACIJENTA - Andjelic, Sladjana Lj; Colakovic, Goran; Emis-Vandlik, Nada A; Djikic Andjelic, Ivana; Velickovic, Nevenka; Jeremic, Miroljub; Ivanovic Tanasijevic, Marina (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Objective And during the COVID 19 pandemic, patients may develop STEMI symptoms. We present a COVID 19 positive patient with prehospital STEMI, differential diagnostic concerns during hospitalization, and the implementation of a high-level safety strategy for healthcare professionals during care.Case report The EMS team transported the STEMI patient to the catheterization room. The patient was examined for anginal pain. Epidemiological surveys on COVID-19 negative. On examination: GCS 15, subfebrile, normotensive, normocardian, eupnoic, SaO2 98%. On ECG STEMI of lateral localization. Placed IV line, prescribed dual antiplatelet therapy. Rapid test is corona positive. Transported directly to the catheterization room. In addition to STEMI, other differential diagnostic diagnoses were considered. As definitive, the diagnosis of Angina pectoris was made. Healthcare workers used personal protective equipment at all levels.Conclusion Sometimes prehospital STEMI is not a definitive diagnosis. A strategy of a high level of safety of health workers is recommended.